Backtracking potential mantle sources of North American kimberlites through kinematic models to constrain their origin - Lee, Esther (Kansas State University, 2023)
Kimberlites are relatively rare ultramafic igneous rocks that are most commonly emplaced on Archean cratons. However, in the North American continent they are widely distributed, including numerous occurrences within younger Proterozoic terranes. Several hypotheses have seen proposed to explain this widespread distribution: entrainment by mantle plumes, fluids derived from subducting slabs, large low shear velocity provinces, and edge-driven convection. In this study, we provide new constraints on North American kimberlite emplacement by backtracking the locus of their emplacement over time using GPlates software to make this reconstruction. We also consider constraints from mantle tomography models and lithosphere-asthenosphere boundary (LAB) models. We show that the youngest kimberlites (ages < 110 Ma) were emplaced through edge-driven convection, while the emplacement of older kimberlites (ages 110-660 Ma) can be accounted for by upwellings originating from LLSVPs. More precisely, kimberlites with ages between 110 and 300 Ma were emplaced over the Atlantic LLSVPs, while older kimberlites (ages 350-660 Ma) were emplaced over the Pacific LLSVPs. The backtracked locations of kimberlites in the Pacific display a westward increase in age. Such a pattern can be created by the drifting of the North America plate over the fixed mantle source and is therefore in agreement with the hypothesis that the emplacement of these kimberlites is related to LLSVPs.
Keywords: backtracking; North American kimberlites; kimberlites; kinematic models; constrain; origin